GENE THERAPY FOR AADC DEFICIENCY (2018)
L11 11 11 LLThe present invention is directed to compositions and methods for treating aromatic -amino acid decarboxylase (AADC) deficiency. This invention includes a method of treating AADC deficiency in a pediatric subject, comprising the steps of: (a) providing a pharmaceutical formulation comprising an rAAV2-hAADC vector, (b) stereotactically delivering the pharmaceutical formulation to at least one target site in the brain of the subject in a dose of an amount at least about 1.8×10vg; wherein delivering the pharmaceutical formulation to the brain is optionally by frameless stereotaxy, and optionally wherein the dose is an amount of at least about 2.4×10vg and in some embodiments wherein the pharmaceutical formulation comprises a rAAV2-hAADC vector concentration of about 5.7×10vg/mL. This invention is also directed to methods for treating aromatic -amino acid decarboxylase (AADC) deficiency, wherein the method optionally further comprises the step of administering a therapeutically effective dose of dopamine-antagonist to the subject such as risperidone. This invention is also directed to methods for treating aromatic -amino acid decarboxylase (AADC) deficiency, wherein the method optionally comprises providing a pharmaceutical formulation comprising an rAAV2-hAADC vector, and empty capsids.